ANALISIS PENGARUH PENATAAN ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DENGAN VARIABEL INTERVENING KEPUASAN KERJA - Budi Wiharto; Kirbrandoko Kirbrandoko; Anwar Rahim (ITB AAS INDONESIA Surakarta, 2021)
This study aims to analyze the influence of organizational arrangements and work motivation on employee performance with intervening variables of work satisfaction in the directorate of high schools, the ministry of education and culture. Quantitative research approach. In instrument testing using validity and reliability tests, data analysis is used using Path Analysis using spss version 23 applications. The results showed that: 1) there is an indirect influence of organizational arrangements on employee performance with intervening variables of job satisfaction, 2) there is an indirect influence of work motivation on employee performance with variable intervening job satisfaction, 3) there is an indirect influence of organizational arrangement and work motivation together on employee performance with intervening variables of job satisfaction, 4) there is no direct influence of organizational arrangements on employee performance, 5) there is a direct influence of work motivation on employee performance in the Directorate of High School, 6) there is a direct influence of job satisfaction on employee performance, and 7) there is a direct influence of organizational arrangement and work motivation together on employee performance with intervening variables of job satisfaction in the Directorate of Senior Secondary Education, Ministry of Education and Culture.